2016
DOI: 10.1364/ome.6.003787
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput in-volume processing in glass with isotropic spatial resolutions in three dimensions

Abstract: Abstract:We report on fabrication of three dimensional (3D) microstructures in glass with isotropic spatial resolutions. To achieve high throughput fabrication, we expand the focal spot size with a low-numerical-aperture lens, which naturally results in a degraded axial resolution. We solve the problem with simultaneous spatial temporal focusing which leads to an isotropic laser-affected volume with a spatial resolution of ~100 m.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…In addition, femtosecond laser has been proven to be able to process various transparent materials such as polymer, glass, crystal, and bio‐tissue . As a matter of fact, we have applied the SSTF method in different materials, such as fused silica and photosensitive Foturan glass . The SSTF‐TPP can also be extended to various types of polymers other than SU‐8, as the key of TPP is to replace the one‐photon UV polymerization with the two‐photon polymerization process; thus, most polymers that could be UV cured should be qualified for the technique presented here.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, femtosecond laser has been proven to be able to process various transparent materials such as polymer, glass, crystal, and bio‐tissue . As a matter of fact, we have applied the SSTF method in different materials, such as fused silica and photosensitive Foturan glass . The SSTF‐TPP can also be extended to various types of polymers other than SU‐8, as the key of TPP is to replace the one‐photon UV polymerization with the two‐photon polymerization process; thus, most polymers that could be UV cured should be qualified for the technique presented here.…”
Section: Resultsmentioning
confidence: 99%
“…Although FLDW can provide the resolution for fabricating the submicrometer-scale channels with a high numerical aperture objective, it will be extremely time-consuming to produce the large chamber at the same fabrication resolution. One solution is to shape the focal spot size spatially and temporally, which can allow for dynamically switching the focal volume size (i.e., equivalent to switching the fabrication resolution) during the fabrication process whilst still ensuring a 3D isotropic resolution even when the numerical aperture of the focusing system varies [ 30 ]. The field will remain active as long as better performances and higher functionalities of 3D micro- and nanofluidics are highly in demand for emerging innovative applications.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…This leads to significant enhancement of the fabrication efficiency due to the realization of high-throughput 3D femtosecond laser fabrication. Figure 7 demonstrates the fabrication of a complex, large-scale 3D model of the China Pavilion of EXPO 2010 (world exhibition of exposition) using the SSTF technique [31]. Despite its large size and the low repetition rate of the femtosecond laser used in the experiment, the structure was completed within a few minutes thanks to the large spherical focal spot produced by SSTF.…”
Section: Applications Of the Sstf Technique In Femtosecond Laser Micrmentioning
confidence: 99%
“…In addition, the aspect ratio of the cross-section can be controlled by changing the spatial chirp before the objective lens through theoretical simulation [19]. More recently, Tan et al reported that a 3D isotropic spatial resolution of 100 μm can be achieved with a low numerical aperture lens by utilizing the spatiotemporal focusing technique [31]. This leads to significant enhancement of the fabrication efficiency due to the realization of high-throughput 3D femtosecond laser fabrication.…”
Section: Applications Of the Sstf Technique In Femtosecond Laser Micrmentioning
confidence: 99%